Effect of particle size on phytochemical composition and antioxidant properties of Sargassum cristaefolium ethanol extract - E. S. Prasedya (Nature Portfolio, 2021)
Abstract Sample particle size is an important parameter in the solid–liquid extraction system of natural products for obtaining their bioactive compounds. This study evaluates the effect of sample particle size on the phytochemical composition and antioxidant activity of brown macroalgae Sargassum cristaefolium. The crude ethanol extract was extracted from dried powders of S.cristeafolium with various particle sizes (> 4000 µm, > 250 µm, > 125 µm, > 45 µm, and < 45 µm). The ethanolic extracts of S.cristaefolium were analysed for Total Phenolic Content (TPC), Total Flavonoid Content (TFC), phenolic compound concentration and antioxidant activities. The extract yield and phytochemical composition were more abundant in smaller particle sizes. Furthermore, the TPC (14.19 ± 2.08 mg GAE/g extract to 43.27 ± 2.56 mg GAE/g extract) and TFC (9.6 ± 1.8 mg QE/g extract to 70.27 ± 3.59 mg QE/g extract) values also significantly increased as particle sizes decreased. In addition, phenolic compounds epicatechin (EC), epicatechin gallate (ECG), epigallocatechin (EGC), and Epigallocatechin gallate (EGCG) concentration were frequently increased in samples of smaller particle sizes based on two-way ANOVA and Tukey’s multiple comparison analysis. These results correlate with the significantly stronger antioxidant activity in samples with smaller particle sizes. The smallest particle size (< 45 µm) demonstrated the strongest antioxidant activity based on DPPH, ABTS, hydroxyl assay and FRAP. In addition, ramp function graph evaluates the desired particle size for maximum phytochemical composition and antioxidant activity is 44 µm. In conclusion, current results show the importance of particle size reduction of macroalgae samples to increase the effectivity of its biological activity.